Source apportionment of fine particulate matter during autumn haze episodes in Shanghai, China. Issue 4 (25th February 2014) - Wang, Yangjun; Li, Li; Chen, Changhong; Huang, Cheng; Huang, Haiying; Feng, Jialiang; Wang, Shuxiao; Wang, Hongli; Zhang, Gangfeng; Zhou, Min; Cheng, Ping; Wu, Minghong; et al.
Abstract Understanding the origin of fine particulate matter is essential to proposing proper strategies for heavy haze mitigation in Shanghai, China. In this study we used the Particulate Matter Source Apportionment Technology in Comprehensive Air Quality Model with Extensions to quantify the impacts of emissions on the concentrations of fine particulate matter (PM2.5) and its important components in Shanghai during heavy haze episodes in late autumn (6–22 November 2010). The factors considered here are regions of Shanghai and its surrounding areas, long‐range regional transport, and different local emission categories. The results indicate that industrial process is the dominant local contributor to total PM2.5 mass in the whole city except that at the urban center vehicle emission contributes slightly more. In addition, industrial process and vehicle emission are the major local contributors for nitrate in Shanghai, although at urban core the contribution from vehicle emission is remarkably larger. Generally, both local contribution and regional transport contribution could dominate a severe haze event in late autumn. However, the dominant contributor could either be local emission or regional transport, usually depending on the meteorological conditions. Therefore, particular attentions should be paid to the emission control in the upwind adjacent provinces, as well as in local areas, for developing effective strategies to reduce PM2.5 pollution in Shanghai.